Cross-site scripting (xss) vulnerability in the cirebon district health service web system - Isma Elan Maulani; Siti Ainul Kholipah; Mamduh Rihadatul Aisy (Publikasi Indonesia, 2024)
In an era of rapid growth in information technology, the enormous benefits generated are also accompanied by significant security risks. This research was conducted by an independent security researcher, Isma Elan Maulani, to identify and analyze security vulnerabilities on the Cirebon District Health Service website. The focus of the research centered on the